Molecular Epidemiology and Antibiotic Resistance Profiles of Methicillin-Resistant Staphylococcus aureus Strains in a Tertiary Hospital in China - Kong, Haishen; Yu, Fei; Zhang, Weili; Li, Xuefen; Wang, Hongxia (Frontiers in Microbiology, 2017)
Analysis of the genotypic characteristics and antimicrobial susceptibility patterns of methicillin-resistant Staphylococcus aureus (MRSA) is essential for the control and treatment of diseases caused by this important pathogen. In this study, MRSA isolates obtained from a tertiary care hospital in China were subjected to spa typing, SCCmec typing, multiple locus sequence typing (MLST) and PCR targeting of the genes encoding Panton-Valentine leukocidin (PVL). The disk diffusion method was used to test the antimicrobial susceptibility of the isolates to ten non-beta-lactam antibiotics. Among the 120 MRSA isolates studied, 18 spa types and 15 ST types were identified. The spa t311 type was the most common (a total of 60 isolates; 50%) among the study strains, and nearly all the t311 strains belonged to ST5, which is the most common ST type that was previously reported from China among the t002 isolates. ST5-II/t311 was the major prevalent clone (55, 45.8%), which was followed by ST5-II/t002 (12, 10.0%) and ST59-IV/t437 (11, 9.2%). PVL-encoding genes were found in 6.7% of the isolates. Although the ST5-II/t311 and ST5-II/t002 clones are different spa types, they shared the same resistance profile (clindamycin, erythromycin and ciprofloxacin). Most isolates of the ST239-III/t037 clone were resistant to clindamycin, erythromycin, ciprofloxacin, gentamicin, tetracycline and trimethoprim/sulfamethoxazole. By contrast, the MRSA isolates of the ST239-III/t030 clone were more resistant to rifampin, but they were susceptible to trimethoprim/sulfamethoxazole. Our data emphasize the need for ongoing epidemiologic surveillance.